1975
DOI: 10.1002/dev.420080205
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory, thermal, and tactual influences on infantile ultrasonic vocalization in rats

Abstract: The amount of time infant rats 3-13 days old spent emitting ultrasounds was greater when pups were placed in an empty dish than when placed in a dish containing clean bedding or soiled bedding from the nest. Pups from 5-13 days of age vocalized more when on the clean bedding than when on the soiled bedding. When placed on cloth covered dishes, pups vocalized most to the empty dish and least to the dish containing soiled bedding. The odor of clean bedding elicited less ultrasonic vocalization than the odor of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
107
1
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(119 citation statements)
references
References 13 publications
10
107
1
1
Order By: Relevance
“…That it does has been known since the very earliest studies [1,80,82]. But the results do show that the function of USV as frequently tested, e.g., during brief isolations at room temperature, is not part of a thermogenic response.…”
Section: Isolation-induced Usv Is Not a By-product Of Thermal Or Cardmentioning
confidence: 83%
See 1 more Smart Citation
“…That it does has been known since the very earliest studies [1,80,82]. But the results do show that the function of USV as frequently tested, e.g., during brief isolations at room temperature, is not part of a thermogenic response.…”
Section: Isolation-induced Usv Is Not a By-product Of Thermal Or Cardmentioning
confidence: 83%
“…The effects of an infant's formation of early life relationships and its social interactions with caretakers are known to last well in to adulthood with both beneficial and harmful effects [28,35,70]. In our laboratory, we study the development of social relationships between infant rats and their dams, sires, and littermates using an isolation, reunion, and re-isolation test paradigm.Infant rats emit ultrasonic vocalizations (USV) in a variety of situations, including as a response to isolation, physical manipulation, and thermal and olfactory challenge [1][2][3]6,19,25,46,79,80,82,97]. Many researchers have used the presence and absence of these sounds to make inferences about the internal state of the rodents, e.g., isolation-induced USV's have often been called "distress vocalizations" [29,76,78].…”
mentioning
confidence: 99%
“…Schapiro and Salas (1970) demonstrated that exposure to maternal odors in rat pups before weaning reduced the movements of pups. Oswalt and Meier (1975) found that infant rats reduce their emission of ultrasonic vocalizations when exposed to maternal odors. Therefore, maternal litter or home odors produce signs of calm.…”
Section: Calming Effects Of Maternal Biological Fluidsmentioning
confidence: 99%
“…Most authors report that, for pups 2 weeks old or older, cues other than temperature come into play and influence the rate of vocalization. These cues include the presence of conspecifics (Hofer & Shair, 1978, 1980, handling or 4-4 tactile cues (Gardner, 1985;Okon, 1972;EIsner et al, 1990), olfactory cues (Conely & Bell, 1978;Oswalt & Meier, 1975;Lyons & Banks, 1982), nutritional cues (Blass & Fitzgerald, 1988;Shide & Blass, 1989), and other contextual factors (e.g., learning, Amsel et al, 1977).…”
Section: B Contextual Factors Influencing Vocalizationsmentioning
confidence: 99%
“…In some of the work of Hofer and colleagues (e.g., Hofer & Shair, 1978;1980), as well as some earlier research (e.g., Oswalt & Meier, 1975) there have been attempts to control various factors and test cues in isolation from one another. Hofer & Shair (1980) found that tactile, temperature, and odor cues were all important in influencing UV emission rate in isolated 2-week-old pups.…”
mentioning
confidence: 99%